2014
DOI: 10.11591/ijai.v3.i1.pp36-48
|View full text |Cite
|
Sign up to set email alerts
|

Quality Model and Artificial Intelligence Base Fuel Ratio Management with Applications to Automotive Engine

Abstract: <p class="Default">In this research, manage the Internal Combustion (IC) engine modeling and a multi-input-multi-output artificial intelligence baseline chattering free sliding mode methodology scheme is developed with guaranteed stability to simultaneously control fuel ratios to desired levels under various air flow disturbances by regulating the mass flow rates of engine PFI and DI injection systems. Nevertheless, developing a small model, for specific controller design purposes, can be done and then v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Process for sending address to mobile phone is GPS take the address in that place based on latitude and longitude sending location then send it to Arduino programming which control between GPS and GSM. GSM send the SMS the information to smart phone [20]. This work was divided into two parts which are the tracking part and the displaying part.…”
Section: System Overviewmentioning
confidence: 99%
“…Process for sending address to mobile phone is GPS take the address in that place based on latitude and longitude sending location then send it to Arduino programming which control between GPS and GSM. GSM send the SMS the information to smart phone [20]. This work was divided into two parts which are the tracking part and the displaying part.…”
Section: System Overviewmentioning
confidence: 99%
“…In a fractional order PID controller using the multi-objective optimization function, the weighted integral time absolute error of individual loops is added together, and the performance rejection is validated by analyzing the response for set point change and interruption [20]. Through MATLAB simulations, a well-tuned baseline multi-loop PID controller was compared to the fuzzy inference baseline sliding methodology and showed that it could simultaneously regulate fuel ratios to appropriate levels under varying airflow disturbances by adjusting the mass flow rates of the port fuel injection (PFI) and direct-injection (DI) engines [21].…”
Section: Introductionmentioning
confidence: 99%